From submission to forlornness: covert exclusion from schooling (Praxis Educativa, 2012)
The return to democracy in Argentina reinstalled a central topic: the education of youngsters as critical and autonomous subjects able to advocate a new way of life. The criticism to learning from memory led in most cases to memory abuse, not only to foster irreflection but also to lead to manipulation from the present hegemony. Illusion defeated research: learning to think as if were possible without knowledge. Memory was condemned as well as school norms. In many cases, trying to dismantle authoritarism led to the ingenuous belief that moral and intellectual autonomy would emerge spontaneous-ly due to the disappearance of “control mechanisms of behaviour” in schools: free from asymetric impositions, schools would become a place in which there is dialogue among equals. Research shows that instead of generating equality, the non-acceptance of authority and know-ledge led to a deepening of inequality.
Keywords: school; submission; abandonment; exclusión; inequality